2008
DOI: 10.1002/jso.20957
|View full text |Cite
|
Sign up to set email alerts
|

Management of hepatic metastasis of gastrointestinal carcinoid tumors

Abstract: Multimodality therapy in the management of hepatic carcinoid metastasis can be done safely and effectively. We recommend the use of hepatic resection when feasible as this treatment most likely offers the best long-term outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 16 publications
2
56
0
1
Order By: Relevance
“…As no neuroendocrine cells have ever been detected in the kidneys, 11 several theories have been proposed as to the exact pathogenesis of renal carcinoid tumours, including urothelial metaplasia, 12 metastases from undiscovered primaries, entrapped neural crest or pancreatic cells and primitive stem cell differentiation. 1,10 Although our patient did not have any anatomical urological abnormalities, the high associations of renal carcinoid with horseshoe kidneys (17.8%) and teratomas (14.3%) suggest that the development of these tumours is related to predisposing embryological factors.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…As no neuroendocrine cells have ever been detected in the kidneys, 11 several theories have been proposed as to the exact pathogenesis of renal carcinoid tumours, including urothelial metaplasia, 12 metastases from undiscovered primaries, entrapped neural crest or pancreatic cells and primitive stem cell differentiation. 1,10 Although our patient did not have any anatomical urological abnormalities, the high associations of renal carcinoid with horseshoe kidneys (17.8%) and teratomas (14.3%) suggest that the development of these tumours is related to predisposing embryological factors.…”
Section: Case Reportmentioning
confidence: 99%
“…11 There is good evidence for survival after excision of involved lymph nodes and resection of metastatic hepatic metastases, but not for debulking of unresectable primary or secondary tumours. 12 The choice of chemotherapeutic agents remains controversial even for the more common gastrointestinal and respiratory carcinoid tumours. Response rates are low, with combination regimens of streptozocin and fluorouracil (33%) or streptazoin and cyclophosphamide (26%), as well as single agents such as fluorouracil, streptozocin, or doxorubicin (20%).…”
Section: Case Reportmentioning
confidence: 99%
“…Similarly, drug-eluting beads with doxorubicin (DEBDOX) has also been found to be safe and effective in the management of metastatic NETs to the liver [7].…”
Section: Introductionmentioning
confidence: 99%
“…Concerning other prognostic parameters for primary NETs and liver metastases, Katz et al demonstrated that the robust presence of tumor-infiltrating lymphocytes is a significant predictor of outcome [44]. Other recent articles confirmed surgical therapy to be the most efficient approach against solitary hepatic metastases [7,8,14,22,23,33,34,40,45,46], with a potential curative resection of liver secondaries can be undertaken in 13.7 to 24.5% of patients with metastatic NETs [47][48][49], and a significant reduction of carcinoid symptoms [43], but the majority of studies focused exclusively on resection rather than combined-modality approaches with ablation or chemotherapy.…”
Section: Liver Metastases From Neuroendocrine Tumorsmentioning
confidence: 99%
“…In fact, metastases are well recognized as being the major cause of death among neoplastic patients, and the prognosis of patients affected by unresectable liver metastases is very poor. However, although once metastatic malignancies were commonly considered as a terminal neoplastic stage, nowadays, many different therapeutical options have been introduced in order to provide a safe and efficient treatment for these kinds of patients and improve both their quantity and quality of life [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%